2013
DOI: 10.1080/02701367.2013.850993
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Physical Activity and Sedentary Behavior of Chinese City Children and Youth Using Accelerometers

Abstract: The findings warn of the insufficiency of PA and the excess of SB in Chinese city children and youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 31 publications
18
84
1
Order By: Relevance
“…However, the results of the present study indicated that only a small percentage of children met the recommended MVPA of 60 minutes per day. The results are consistent with previous physical activity studies among Chinese children and adolescents (Shi et al, 2006;Tudor-Locke et al, 2003;Wang et al, 2013). Several studies have reported that Chinese children are inactive because they do not perform household chores and they are under extreme pressure to succeed academically (Tudor-Locke et al, 2003;Wang et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, the results of the present study indicated that only a small percentage of children met the recommended MVPA of 60 minutes per day. The results are consistent with previous physical activity studies among Chinese children and adolescents (Shi et al, 2006;Tudor-Locke et al, 2003;Wang et al, 2013). Several studies have reported that Chinese children are inactive because they do not perform household chores and they are under extreme pressure to succeed academically (Tudor-Locke et al, 2003;Wang et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
“…The results are consistent with previous physical activity studies among Chinese children and adolescents (Shi et al, 2006;Tudor-Locke et al, 2003;Wang et al, 2013). Several studies have reported that Chinese children are inactive because they do not perform household chores and they are under extreme pressure to succeed academically (Tudor-Locke et al, 2003;Wang et al, 2013). In this study, the mean score of two types of parental support was higher than the midpoint, which indicated that the parental support of children's MVPA was generally positive.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Children in this study reported a slightly higher MVPA level (43.1 ± 12.7 min) than Chinese children in another study (28.3 ± 17.7 min) due to the adoption of different cut-points for MVPA (≥2296 CPM in the current study vs. ≥2800 CPM in the other study) [4]. Considering the PA level assessed by accelerometer was sensitive to the cutoff points defining activity intensity, the results from studies using different cutoff points would therefore not be comparable.…”
Section: Discussionmentioning
confidence: 80%
“…A national survey using accelerometers revealed that Chinese children and youth spent an average of 28.3 min per day in MVPA. Only 9.4% of boys and 1.9% of girls met the recommendation of 60 min/day of MVPA [4]. Similarly, in Hong Kong, only 8.3% of children aged 7–12 years engaged in the recommended PA levels [5].…”
Section: Introductionmentioning
confidence: 99%